PENGARUH PERBANDINGAN SEMOLINA DAN TEPUNG BERAS HITAM TERHADAP KARAKTERISTIK PASTA FETTUCINE BASAH - Wulandari, Ni Kadek Nova; Ekawati, I Gusti Ayu; Putra, I Nengah Kencana (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2019)
This study aims to determine the effect ratio of semolina and black rice flour to the characteristics of wet fettucine paste and to know the right ratio for semolina and black rice flour to produce wet fettucine paste with the best characteristics. This study used a Completely Randomized Design (RAL) with a comparison treatment of semolina and black rice flour : 100% : 0%; 90% : 10%; 80% : 20%; 70% : 30%; 60% : 40%; and 50% : 50%. The treatment was repeated 3 times to obtain 18 units of the experiment. The data obtained were analyzed by variance and if there was influence between treatments followed by Duncan test. The results showed that the use of semolina and black rice flour had significant effect on water content, ash content, antioxidant capacity, total anthocyanin, flavor, taste, texture, and overall acceptance of wet fettucine pasta. Ratio of 50% semolina and 50% black rice flour had the best characteristics with 56,49% water content, 0.69% ash content, 2.26 mg/100g total anthocyanin, 23.02% antioxidant capacity, color purplish black and ordinary, texture rather supple and rather liked, flavor rather liked, taste rather liked and overall acceptance ordinary.